Atlantoaxial epidural abscess secondary to grass awn migration in a dog - Linon, E.; Geissbühler, U.; Karli, P.; Forterre, F. (Veterinary and Comparative Orthopaedics and Traumatology, 2014)
A two-year-old female Lucerne Hound was presented with a one-week history of signs of progressive neck pain, inappetence, apathy, and an elevated rectal temperature. Findings of magnetic resonance imaging (MRI) were consistent with a foreign body abscess in the epidural space at the level of the first and second cervical vertebrae. A leftsided dorso-lateral atlantoaxial approach was performed, revealing an epidural abscess containing a grass awn. The clinical signs resolved within three days of surgery and the dog made a full recovery. This case report shows that grass awns can migrate to the atlantoaxial region in dogs and MRI findings lead to a suspicion of caudo-cranial migration within the spinal canal.
Keywords: Epidural abscess; dog; foreign body; MRI; atlantoaxial